2021
DOI: 10.1093/jncics/pkab013
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of APOE ε2 Genotype on Cognition in Older Breast Cancer Survivors: The Thinking and Living With Cancer Study

Abstract: Background Cancer-related cognitive decline (CRCD) has been linked to apolipoprotein E (APOE) gene ε4 polymorphisms. APOE ε4 polymorphisms are also the strongest genetic risk for late-onset Alzheimer’s disease (AD), while ε2 polymorphisms protect against AD. However, the effects of ε2 polymorphisms on CRCD have not been evaluated. Methods We evaluated non-metastatic breast cancer survivors (n = 427) and matched non-cancer con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The result showed that the top 20 proteins interacting with AHSG (Figure 9B ) mainly functioned in tumor suppressor, signal transduce, cancer development. 26 , 27 , 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that the top 20 proteins interacting with AHSG (Figure 9B ) mainly functioned in tumor suppressor, signal transduce, cancer development. 26 , 27 , 29 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39…”
Section: Resultsmentioning
confidence: 99%
“…The top 20 proteins interacting with AHSG by GeneMANIA were partially associated with tumor development or tumor suppression, which also suggests that AHSG is a potential key gene for chRCC. 26 , 27 , 29 , 30 , 33 , 34 , 35 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…While FOXN2 has not been specifically identified in neurodegenerative disease or cognitive functional research, perturbations in these molecular pathways have been identified in Alzheimer's disease as well as cancer 30 . Additionally, rs78786199 is in a predicted binding site for several transcription factors, including Zinc Finger Imprinted 3,Interferon Regulatory Factors 1,4,7,and 8,Signal Transducer and Activator of Transcription 2, and Zinc Finger Protein 317. These transcription factors regulate numerous cellular processes, including hematopoiesis, inflammation, immune responses, cell proliferation, regulation of the cell cycle, and induction of growth arrest and programmed cell death in response to DNA damage, suggesting multiple mechanisms that could connect this locus with cancer and CRCD [31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Raw scores were standardized using the control group mean and standard deviation at baseline stratified by age and education. Standardized scores were then used to calculate z-scores for each domain for every participant, as described previously 11,12 . These domains were chosen because research has shown them to be relevant to CRCD 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation